Meningkatkan Kesejahteraan Masyarakat Kebonagung Dengan Cara Mengoptimalisasikan Koperasi Syari’ah: (Studi Analisis Badan Amil Zakat RW. 03 Desa Kebonagung Kecamatan Pakisaji Kabupaten Malang) - Choirul Kurniawan (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
In accordance with the Regulation of the Minister of Cooperatives and Small and Medium Enterprises Number: 16/Per/M.KUKM/IX/2015 that cooperatives have the goal of prospering members in particular and society in general, as well as participating in building a national economic order in order to createad eveloped, fair society, and prosperous based on Pancasila and the 1945 Constitution. Therefore, the writer needs to raise the object of research on the Islamic cooperative which was founded in 2005 which is managed by BAZ RW. 03 Kebonagung in order to improve the welfare of the surrounding community and as a source of inspiration for readers. This research method is qualitative, in which the writer tries to present a descriptive description of how this Islamic cooperative operates and begins by collecting primary data about history, licensing, structure, products, business capital, and constraints. To facilitate this research, the authors use research methods including: interviews, observation, documentation, and questionnaire tests. The results of this study are expected to provide information for readers as an insight into the management of Islamic cooperatives and provide understanding to the community of the benefits of Islamic cooperatives and avoiding usury. From the above discussion, it can be concluded that with good intentions and accompanied by a noble social and human spirit, efforts must be accompanied by adequate knowledge but must be in accordance with the teachings of Islamic law. Like wise with the Amil Zakat Board (BAZ) in RW. 03 Desa Kebonagung Kec. Pakisaji Kab. Malang. It is unfortunate that running an advanced cooperative not only has sufficient capital, but tenacity and assistance for business actors must also be improved.